2004
DOI: 10.1258/0022215042450733
|View full text |Cite
|
Sign up to set email alerts
|

2′,5′-Oligoadenylate synthetase activity analysis and human papilloma virus typing as prognostic factors in patients with recurrent respiratory papillomatosis

Abstract: Patients with HPV type 11, a severity score >4, a high number of surgical procedures prior to interferon-alpha therapy and a high basal 2',5'-oligoadenylate synthetase activity should be considered at high risk of an aggressive clinical course, often with spread to lower airway passages, malignant transformation and death. Human papilloma virus type, score for recurrent respiratory papillomatosis severity, number of surgical procedures and 2',5'-oligoadenylate synthetase activity showed significant association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In half of them, the onset of the disease was before the first year of age. In the patients with non-aggressive course, the mean age of the disease onset was 5 years and 6 months, which corroborates the literature data [15].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In half of them, the onset of the disease was before the first year of age. In the patients with non-aggressive course, the mean age of the disease onset was 5 years and 6 months, which corroborates the literature data [15].…”
Section: Discussionsupporting
confidence: 89%
“…In one study patients with disease onset <3 years had more severe disease, as measured by the mean number of the performed surgical procedures and by the number of the affected anatomical sites [15]. It has been suggested that the link between the young age at disease onset and the disease aggressiveness may be explained by immaturity of the immune response mechanisms [15].…”
Section: Discussionmentioning
confidence: 99%
“…Up to 3% of children with RRP will die of the disease [6]. The well-known negative prognostic factors of respiratory papillomatosis are early disease onset, high number of surgeries per year and HPV type 11 infection [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…High recurrence rate and tendency to spread throughout the respiratory tract make it difficult to treat, especially in cases associated with a long course of the disease and a malignant transformation [1,2]. The viral etiology of RRP [3] and the role of HPV type 6 and HPV type 11 in the course and prognosis of RRP are ultimately determined [4,5]. However, over the last years, an increase in the lifetime of patients even with severe forms of RRP, has been observed.…”
Section: Introductionmentioning
confidence: 99%
“…HPV type 11 infection itself confers a more aggressive course on RRP. It is marked by worse long-term response to therapy, higher incidence of malignant transformation and mortality during long-term observation [1,2,5]. Affected patients demonstrate a longer period of disease activity and are less likely to go into remission compared to patients infected with HPV type 6.…”
mentioning
confidence: 99%